Comparative studies between mice molars and incisors are required to draw an overview of enamel structural complexity - Goldberg, Michel; Kellermann, O.; Dimitrova-Nakov, S.; Harichane, Y.; Baudry, A. (Frontiers in Physiology, 2014)
In the field of dentistry, the murine incisor has long been considered as an outstanding model to study amelogenesis. However, it clearly appears that enamel from wild type mouse incisors and molars presents several structural differences. In incisor, exclusively radial enamel is observed. In molars, enamel displays a high level of complexity since the inner part is lamellar whereas the outer enamel shows radial and tangential structures. Recently, the serotonin 2B receptor (5-HT2BR) was shown to be involved in ameloblast function and enamel mineralization. The incisors from 5HT2BR knockout (KO) mice exhibit mineralization defects mostly in the outer maturation zone and porous matrix network in the inner zone. In the molars, the mutation affects both secretory and maturation stages of amelogenesis since pronounced alterations concern overall enamel structures. Molars from 5HT2BR KO mice display reduction in enamel thickness, alterations of inner enamel architecture including defects in Hunter-Schreger Bands arrangements, and altered maturation of the outer radial enamel. Differences of enamel structure were also observed between incisor and molar from other KO mice depleted for genes encoding enamel extracellular matrix proteins.